A disciplina 'Comunicação e Diversidade' nos cursos de Relações Públicas das universidades brasileiras - Evangelista, Mateus Pacheco Braga (Brasil, 2023)
This study presents the results on the perspectives of the diversity theme in the training of Public Relations professionals through the insertion of the college subject Communication and Diversity in undergraduate courses in Brazilian universities. Initially, research was conducted on the genesis of Public Relations, as well as on the emergence of undergraduate courses and the evolution of curricular guidelines in the area. Themes such as communications, sustainability, and diversity, which underlie and conceptualize the main theme of this research, were also addressed. Communication and Diversity in college education was then discussed, through an analysis of the insertion of this subject in the curricular structure of Public Relations school. To achieve the goal of this study, the methodology adopted was bibliographic research which allowed the study on the theme, as well as documentary research for the analysis of official documents of the institutions covered in the universe of this paper. It was identified that undergraduate courses in PR, in general, do not offer subjects related to Communication and Diversity in their curricula, having a minimum percentage that makes a direct or indirect approach to the theme. At last, this study elaborates a suggestion for the discipline Communication and Diversity to be inserted in the updating of the Federal University of Amazonas Public Relations course curriculum guidelines.